Динаміка показників біоелектричної активності головного мозку у хворих з віддаленими наслідками легкої черепно-мозкової травми під впливом програмованої сенсорної деривації = Dynamics of indicators of bioelectric activity of brain in patients with remote consequences of mild traumatic brain injury influenced programmable sensory deprivation = Динамика показателей биоэлектрической активности головного мозга у больных с отдаленными последствиями легкой черепно-мозговой травмы под. влиянием программируемой сенсорной депривации - Donnyk, T. A. (Journal of Education, Health and Sport, 2016)
Donnyk T. A. Динаміка показників біоелектричної активності головного мозку у хворих з віддаленими наслідками легкої черепно-мозкової травми під впливом програмованої сенсорної деривації = Dynamics of indicators of bioelectric activity of brain in patients with remote consequences of mild traumatic brain injury influenced programmable sensory deprivation = Динамика показателей биоэлектрической активности головного мозга у больных с отдаленными последствиями легкой черепно-мозговой травмы под. влиянием программируемой сенсорной депривации Journal of Education, Health and Sport. 2016;6(10):493-500. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164867 http://ojs.ukw.edu.pl/index.php/johs/article/view/3983 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. УДК 616.8-092.6-001 Динаміка показників біоелектричної активності головного мозку у хворих з віддаленими наслідками легкої черепно-мозкової травми під впливом програмованої сенсорної деривації Т. А. Донник Харківська міська клінічна багатопрофільна лікарня № 25 Резюме В статті вивчено динаміку біоелектричної активності головного мозку у хворих з наслідками легкої черепно-мозкової травми до- та після програмованої сенсорної депривації. Внутрисистемна дезінтеграція діяльності ЦНС визначається порушенням співвідношення між активуючими та дезактивуючими системами мозку, про що свідчить на ЕЕГ депресія α-ритму в поєднанні з наростанням β-активності, це прояви переважання активуючих процесів в інтегративній діяльності мозку. Визначена органічна недостатність в області глибинних структур мозку, що порушує механізми регуляції, знижує адаптивні можливості цих хворих, а це може призводити до погіршення якості їх життя. Доведено, що програмована сенсорна депривація впливає на діяльність системи підкірки, стовбура мозку та структур гіпоталамічної області, що сприяє відновленню збалансованості та інтегрованості функціональної активності цих центрів та знижується активуючий вплив ретикулярної формації на коркові центри регулювання. Ключові слова: програмована сенсорна депривація, наслідки легкої черепно-мозкової травми, біоелектрична активність головного мозку. Dynamics of indicators of bioelectric activity of brain in patients with remote consequences of mild traumatic brain injury influenced programmable sensory deprivation T. A. Donnyk Kharkiv City Clinical Hospital № 25 Multidisciplinary Abstract The paper studied the dynamics of brain activity in patients with consequences of mild traumatic brain injury before and after programirovat sensory deprivation. Intersystem disintegration is determined by the relationship between the violation of activated and deactivated brain systems, which testifies about the α-rhythm depression combined with knots in β-activity, are manifestations of the prevalence of activating processes in the integrative activity of the brain. Revealed an organic insufficiency in the deep structures of the brain that disrupts the regulation mechanisms sigean adaptive capacity of these patients, and this may lead to a deterioration in their quality of life. It is proved that programirovat sensory deprivation affects subcortical system of the brain stem structures and the hypothalamic region that helps to restore zbalansirovannosti and integration of the functional activity of these structures and reduced activating influence of the reticular formation on cortical control centers. Key words: programmed sensory deprivation, the consequences of mild traumatic brain injury, bioelectric activity of the brain.